Implementation of Wordwall Interactive Media in The Digital Age to Improve Numeracy Skills in Students at SDN Mangaran 04 - Falestin Al-zakiyah Prastzuba; Fatqurhohman Fatqurhohman; Nurul Imamah (JTMT: Journal Tadris Matematika, 2025)
This study aims to improve the numeracy skills of fifth-grade students at SDN Mangaran 04 through the application of Wordwall-based interactive learning media. The main problems faced are low numeracy skills among students, particularly in understanding the meaning of numbers in story problems, accuracy in basic arithmetic operations, and simple reasoning skills in determining solution strategies. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, which was carried out in two cycles. The research subjects consisted of 30 fifth-grade students. Data were collected through numeracy tests, observations, and interviews, then analyzed descriptively, quantitatively, and qualitatively. The results showed an increase in students' numeracy skills after the implementation of Wordwall, marked by an increase in the average numeracy score from 22 in the pre-cycle to 80 at the end of Cycle II, as well as an increase in learning completeness from 22% to 80%. This improvement occurred because Wordwall facilitated repetitive numeracy exercises, presented contextual questions through gamification, and provided immediate feedback that helped students correct their mistakes and strengthen their understanding of concepts. Thus, the use of Wordwall-based interactive learning media was found to contribute positively to the improvement of elementary school students' numeracy skills, especially in the context of schools in areas with limited learning facilities.